Efektivitas Pembelajaran Quiz-Quiz Trade dalam Meningkatkan Kepercayaan Diri Berkomunikasi Peserta Didik SMP: Perspektif Erik Erikson - Silviyah, Dailmatus; Ahmadi, Anas (FKIP Universitas Wisnuwardhana, 2024)
Self-confidence in communication is an important aspect that supports the success of social interactions and the psychosocial development of students. This study aims to evaluate the effectiveness of the Quiz-Quiz Trade learning model in enhancing the self-confidence in communication of junior high school students from Erik Erikson's psychosocial perspective. The research employs a quantitative experimental design with two cycles. Each cycle involves pre-tests and post-tests administered to both control and experimental classes. The control class uses a conventional learning model, while the experimental class implements the Quiz-Quiz Trade learning model. Data analysis results show a significant increase in the average self-confidence scores in communication of students after applying the Quiz-Quiz Trade learning model. In the control class, the average score increased from 29.15 (pre-test) to 30.2 (post-test), whereas in the experimental class, the increase was more significant, from 29.95 (pre-test) to 39.05 (post-test). From Erikson's perspective, the application of the Quiz-Quiz Trade learning model not only enhances students' self-confidence in communication but also significantly contributes to their psychosocial development. By receiving positive feedback, this model supports the process of forming a more solid identity and reduces role confusion.